Corporate Social Responsibility/Sustainability in Shipping-Maritime - Marine Environmental Mitigation in a ''Green'' Know-How Study and Greek Perspectives - Pektasoglou Maria
Acknowledgements, Abstract, Literature Review, Introduction, Introduction - Motivation, Globalization and Shipping, Brief Description of Ship Types, Introduction to Marine Safety, Overview, Corporate Social Responsibility, ''Auditoriums'' and Greek Perspectives, Overview, Marine Environmental Issues, The ''Greek'' Effect, Introduction, Overview, Methodology, Results, Conclusion-Suggestions, References.